Journal Information and Editorial Board - Volume 4, Issue 1, 2019 - Science, Idealogy Journal of Arts and Social (Idealogy Journal; Vol 4 No 1 (2019): Idealogy Journal (April 2019)DO - 10.24191/idealogy.v4i1.277, 2021)
No Abstract